How an Audit of Epidural Patients in a Community Hospital Setting Resulted in the Development of a Formal Acute Pain Management Service - David H Goldstein; Elizabeth G VanDenKerkhof; Rebecca Sherlock; Judy Sherlock; Susan Harper (Pain Research and Management)
PURPOSE: To describe the results of an audit of patients who received epidural analgesics postoperatively and the subsequent development of a formal acute pain management service in a community hospital.